Polydimethylsiloxane extraction from silicone rubber into baked goods detected by direct analysis in real-time mass spectrometry - Gross, Jürgen H. (European journal of mass spectrometry, 2015)
Flexible baking molds and other household utensils are made of polydimethylsiloxane (PDMS), also known as silicone rubber. PDMS is prone to release oligomers upon elongated contact with fats, e.g., in the process of baking dough. Positive-ion direct analysis in real time (DART) mass spectrometry (MS) provides an efficient tool for the analysis of PDMS up to m/z 3000. Here, DART ionization is employed in combination with Fourier transform ion cyclotron resonance MS to detect PDMS released into muffins when baked in silicone rubber baking molds. Intensive signals caused by PDMS do occur in the m/z 700-1500 range of DART mass spectra obtained from the crusty surface of muffins after the use of such silicone rubber molds. In addition, triacylglyceroles (TAGs) present as natural ingredients of the analyzed muffins were detected as [TAG+NH4]+ ions.
Gesehen am 11.01.2021